2020
DOI: 10.1111/bjd.18987
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies looking at quality of life and psychological impact in people with photodermatoses – skin diseases triggered by sunlight

Abstract: Summary Photodermatoses, or photosensitivity conditions, are a group of skin disorders caused by exposure to sunlight, overall affecting a large number of people. They cause a range of distressing symptoms including pain and burn, and can make the skin blister, flake and scar. The conditions themselves and the need for patients to avoid and protect themselves from sunlight may affect quality of life and psychological health. This study, from the U.K., aimed to find out what methods of assessment (tools) have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…It is encouraging to see that afamelanotide treatment results in significant improvements on social functioning, giving EPP patients the opportunity to finally participate in more ‘normal’ activities. The findings of this study are in line with previous studies regarding the quality of life in photodermatosis in general, which has shown a very large impact on QoL, with particular effects on employment and social and leisure activities, next to suggested higher anxiety and depression levels 32,33 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is encouraging to see that afamelanotide treatment results in significant improvements on social functioning, giving EPP patients the opportunity to finally participate in more ‘normal’ activities. The findings of this study are in line with previous studies regarding the quality of life in photodermatosis in general, which has shown a very large impact on QoL, with particular effects on employment and social and leisure activities, next to suggested higher anxiety and depression levels 32,33 …”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study are in line with previous studies regarding the quality of life in photodermatosis in general, which has shown a very large impact on QoL, with particular effects on employment and social and leisure activities, next to suggested higher anxiety and depression levels. 32,33 This EPP cohort is comparable in age, contribution of males and females, and ethnicity to previously reported cohorts. 2,28,34,35 It is important to note that more than a third of the patients also report EPP symptoms during autumn and winter, considering the fact that afamelanotide prescriptions are restricted to maximum four times a year.…”
Section: F I G U R Esupporting
confidence: 61%
“…Photodermatoses have a considerable negative impact on quality of life and psychological well‐being 4,5 . A recent systematic review found one‐third of patients with photodermatoses experienced a ‘very large’ or ‘extremely large’ impact on quality of life; that is, with a Dermatology Life Quality Index (DLQI) score > 10 6 . Patients experience a range of distressing symptoms upon or following sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Central to the management of many photodermatoses is advice to reduce sun exposure in the summer months, which may involve behavioural modification such as staying indoors, extensively covering the skin and frequent application of sunscreen, in order to avoid triggering or exacerbating disease. These preventive measures themselves contribute to a significant psychological, social and economic impact, including reduced levels of employment 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…According to the definition adopted by the American Commission on Chronic Illness, chronic disorders are those disorders or deviations from the norm that have one or more of the following characteristics: they have a long or lasting course; their aetiology, course and treatment are not clearly defined; they leave behind a dysfunction or disability; and they require specialised management. Thus, such people must cope not only with the side effects of treatment in the physical dimension, such asa significant decrease in immunity, general weakness of the body and thus a decrease in physical condition, but also in the mental and social dimensions, such as accepting changes in body appearance and changes in functioning in social roles [14,15].…”
Section: Introductionmentioning
confidence: 99%